2018
DOI: 10.1002/app.46430
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of antifouling and antibacterial polysulfone ultrafiltration membranes incorporated with a silver–polydopamine nanohybrid

Abstract: A silver–polydopamine (Ag–PDA) nanohybird was used to produce polysulfone (PSf) ultrafiltration membranes with excellent antifouling and antibacterial properties. First, the catechol functional groups of polydopamine (PDA) helped with the in situ immobilization of silver (Ag) nanoparticles (<10 nm) on the PDA sphere surface; this led to the formation of the Ag–PDA nanohybrid. Then, Ag–PDA/PSf hybrid membranes were prepared via the phase‐inversion method, and the influence of Ag–PDA loading on the hybrid membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The TNTs were prepared from anatase TiO 2 powder using a hydrothermal method . Ag‐NPs were deposited onto TNTs using a photoreduction approach described elsewhere . In brief, a suspension of 0.5 g of TNTs in 50 mL of 100 mM AgNO 3 solution was irradiated using a low‐pressure mercury vapour lamp (TNN 15/32, Heraeus Noblelight GmbH, 15 W, λ max = 254 nm) for 2 h with continuous stirring (250 rpm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TNTs were prepared from anatase TiO 2 powder using a hydrothermal method . Ag‐NPs were deposited onto TNTs using a photoreduction approach described elsewhere . In brief, a suspension of 0.5 g of TNTs in 50 mL of 100 mM AgNO 3 solution was irradiated using a low‐pressure mercury vapour lamp (TNN 15/32, Heraeus Noblelight GmbH, 15 W, λ max = 254 nm) for 2 h with continuous stirring (250 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…Park et al have confirmed that the implementation of polyamide‐based membranes with silver nanoparticles (Ag‐NPs) had a positive impact not only on the antimicrobial activity of the modified membranes, but also on their hydraulic resistance and separation performance. Similar observations were made by Wu et al while studying silver–polydopamine (Ag‐PDA)‐modified PSU membranes. Aside from good separation performance, including an increased pure water flux (PWF) and a well‐maintained bovine serum albumin rejection, the Ag‐PDA‐modified PSU membranes presented an enhanced protein‐fouling resistance and a good antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies [13][14][15][16][17][18][19][20][21], in situ modification of the membrane via biocides is an effective method to prevent the deposition of bacteria on the membrane surface and subsequently to mitigate the biofouling. Silver nanoparticles (AgNPs) are commonly used as the biocide owing to their strong antibacterial activity against numerous types of bacteria [13].…”
Section: Introductionmentioning
confidence: 99%
“…The designs of membrane elements can be in the form of flat films, corrugated elements, tubes, and cartridges. Films made of cellulose acetate, nylon 66, nylon 6, polyvinylidene fluoride, polysulfone, polypropylene, and polyether sulfone are used as membrane materials [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%